Design of biological gene information collection system based on data mining technology - Wu, Yuanjun; Mu, Xiaotong; Kahrizi, Danial (Cellular and Molecular Biology, 2020)
At present, bioinformatics research focuses on the development from the accumulation of biological data to the integration and processing of biological data. This paper designs a bio gene information collection system based on data mining technology. In the system, the information of gene web analysis database, data mining model database and gene chip database is transferred to gene algorithm tool library, which can extract, transform and load the biological gene information, transfer the collected and processed biological gene information to gene general chip and web database analysis logic, and pass it to gene expression spectrum chip/data mining module through API function GUI, through the data mining module GUI feedback to the system users. The system hardware stores the biochip information in the virtual chip set model through the gene expression spectrum data analysis model uses the gene expression similarity analysis model to analyze the expression similarity of the biological gene information, and stores the information in the gene chip database; through the multi-layer structure model, constructs the web genome biochip including the application layer, the data processing layer and the representation layer. The information analysis module analyzes the biological gene information and stores the information in the gene web analysis database. The system software adopts the method of automatic collection of biological gene data based on the web to realize the collection of biological gene information, and gives the main implementation technology of the system. The experimental results show that the system can effectively collect biological gene information, and has high accuracy and anti-noise performance.